Nursing care of infants born extremely preterm. Issue 3 (June 2022) - Karlsson, Victoria; Blomqvist, Ylva Thernström; Ågren, Johan
Abstract: With improving survival at the lowest gestations an increasing number of tiny and vulnerable infants are being cared for, and optimal outcomes require an approach to care that takes their specific characteristics into account. These include immature organ function and a risk for iatrogenic injury, and parental/familial strain due to the high degree of uncertainty, infant-mother separation, and long hospital stay. While the challenges in providing nursing care to these infants are obvious it is also clear that this field has tremendous potential to influence both short and long-term outcomes of this population. This mini-review discusses aspects of the nursing care provided to infants born at the very lowest gestations and their families, with focus on doing less harm by establishing an adequate care environment, actively promoting parental closeness and care-giving, and conservative skin care.